TRUST AND THE THIRD-PERSON POINT OF VIEW: AN EXAMPLE IN TV SERIES - González García, Sara (Analysis. Journal of Philosophical Research, 2024)
The article analyzes trust from an analytical philosophical perspective, with an emphasis on the third-person viewpoint, exemplified through TV series such as Dexter, House of Cards, and Yellowstone 1883/1923. Trust is broken down into three dimensions: self-trust (first person), mutual trust (second person), and trust in institutions or experts (third person). This last type is crucial in the analysis, distinguished by its objectivity and external evaluation based on criteria such as honesty, competence, and responsibility. The article concludes that the dynamics of trust in cultural narratives reflect essential aspects of epistemology and help us understand how we perceive institutions, experts, and cultural stories.